Offering effective feedback to trainees. (January 2015) - Iskander, Morkos
Abstract Effective feedback on performance is an integral part of clinical training. It allows the trainee to critically reflect on their development, as well as enable the teacher to chart progress and detect areas for development. In order to provide effective feedback, we need to take into account the performance itself, but also the setting where feedback is offered, and the expected outcomes of the encounter. As ever, negative feedback remains more difficult to give and receive, and as such requires a greater degree of delicacy to produce a positive result.